Gender and social inclusivity analysis in the common bean seed system in Burundi - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu (2022)
Increasing agricultural productivity, food security and nutrition require inclusive seed systems that delivers quality seed to farmers. However, seed systems development in sub-Saharan Africa often focuses on needs of the large commercial producers, rather than the needs of the smallholder farmers, especially women. This study assessed gender issues in Burundi's seed common bean seed sector to generate gender-specific indicators that can guide development of inclusive seed systems. The results indicated that despite women allocating more land areas to bean varieties, they had limited array of sources of seed and accessed lower volumes of seed from formal outlets. Increasing access to agricultural extension services and training for women, ensuring that women farmers have access to quality seed varieties, providing access to financial services, such as credit and loans, for women farmers, and increasing access to markets for women farmers could enable Burundi seed systems to become more gender inclusive.